The Penguin Classics book - Eliot, Henry (Particular Books, 2018)
"Penguin Classics is the largest and best-known classics imprint in the world. The Penguin Classics Book covers all the greatest works of fiction, poetry, drama, history, and philosophy in between, this reader's companion encompasses 500 authors, 1,200 books, and 4,000 years of world literature, from ancient Mesopotamia to World War I. Filled with stories of the series' UK origin, author biographies, short book summaries and recommendations, and illustrated with historic Penguin Classic covers, The Penguin Classics Book is an entertaining historic look at the earliest chapters of the world's best-known Classics publisher."--Amazon.com